Evaluation and improvement of agronomic practices. Economics - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Economics research in the bean program continues to concentrate on production studies, marketing issues, policy analysis, and training. Diagnostic studies of current production systems and problems were conducted in Brazil, Colombia, Costa Rica, Dominican Republic, El Salvador, Nicaragua, and Peru. Results of preadoption evaluations in Peru and of adoption studies in Guatemala are included. To assess the distribution of benefits of alternative technologies biased towards small or towards large farmers, both among producer groups as well as among consumers of different income strata, a demand and supply model of beans was constructed for Brazil. The model shows that benefits to small farmers are highly sensitive to the degree of technology bias. Most of this research is conducted in collaboration with national programs, and strengthening their research capacity through training and joint projects is a major objective. (CIAT)